Pengaruh Rasio Likuiditas, Profitabilitas, Dan Leverage terhadap Harga Saham Dengan Kebijakan Dividen Sebagai Variabel Moderasi Pada Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2022 - Ayu Putri Anggraini; Ratnawati Raflis (CV. ITTC INDONESIA, 2024)
Financial ratios have an important influence in becoming the basis for investment decision making by investors. Other factors such as dividend distribution and share price also strengthen the reasons for investing in a company. Companies that show good financial ratios will influence investor interest as well as information about large dividend distributions. By attracting investors who invest in the company, the share price will be able to increase. This research aims to determine the effect of liquidity (CR), profitability (ROA), and leverage (DER) on share prices in telecommunications companies in 2020-2022. The research uses dividend policy (DPR) as a moderating variable. The population in this research are all telecommunications companies listed on the Indonesian Stock Exchange. The sample in this research was obtained from 9 telecommunications companies using the purposive sampling method. The analysis techniques used in this research are multiple linear regression and Moderated Regression Analysis (MRA). The results of the hypothesis test show that partially Liquidity (CR) has a positive and significant effect on stock prices with a regression coefficient value of 2625.340 and a significance value of 0.001 which is smaller than 0.05, while profitability (ROA) has a significance value of 0.124 which is greater than 0. 05 and the significance value of leverage (DER), namely 0.151, is greater than 0.05, thus profitability and leverage do not have a significant effect on share prices. Then, with the Z variable as a moderating variable, namely dividend policy, results were obtained that were not significant for share prices on liquidity with a significance value of 0.872 greater than 0.05, profitability with a significance value of 0.679 greater than 0.05, and leverage with a significance value 0.988 is greater than 0.05.